Inquiry in a virtual world: integrating the Zep Quiz game into inquiry-based learning to strengthen learning activeness and critical thinking among vocational students - Richa Witavia S.; Fetri Yeni J.; Alwen Bentri; Mutiara Felicita Amsal (JPI: Jurnal Pustaka Indonesia, 2026)
Vocational students in Indonesia are expected to reason scientifically and participate actively, yet many struggle once a task moves beyond recall. This study tested whether an inquiry-based learning (IBL) sequence built around Zep Quiz, a virtual-world quiz game, could raise learning activeness and critical thinking. A quasi-experimental non-equivalent control group design used two intact Grade 10 classes at SMK Negeri 1 Painan (n = 30 each). The experimental class learned through six IBL stages mediated by Zep Quiz; the control class followed an activity-based routine. Activeness was measured with a Likert questionnaire and critical thinking with a higher-order thinking test. After confirming normality, homogeneity, and baseline equivalence, paired- and independent-samples t-tests and normalized gain were computed. Both groups improved, but the experimental group improved far more. Normalized gains reached the medium-to-high band for the experimental class (activeness ⟨g⟩ = .67; critical thinking ⟨g⟩ = .66) against low gains for the control class (.25 and .31). Post-test differences were large and significant for both activeness (t(58) = 10.67, d = 2.76) and critical thinking (t(58) = 7.19, d = 1.86), both p < .001. Embedding a virtual-world game inside a disciplined inquiry cycle appears a workable route to deeper engagement and higher-order reasoning in vocational science.